231PCost-effectiveness of olaparib vs routine surveillance in the maintenance setting for patients with BRCA-mutated advanced ovarian cancer after response to first-line platinum-based chemotherapy in Singapore. (24th November 2019) - Tan, D S; Chan, J J; Loke, J K; Hettle, R; Ghosh, W; Viswambaram, A; Yu, C C
Abstract: Background: In the randomized, double-blind, phase 3 trial SOLO1, olaparib (OLA) in the maintenance setting demonstrated a 70% lower risk of disease progression or death than placebo in women with newly diagnosed advanced ovarian cancer and a BRCA1/2 mutation. This study aimed to evaluate the cost-effectiveness of OLA maintenance therapy versus routine surveillance (RS) after response to first-line platinum-based chemotherapy in this population in Singapore. Methods: A three-state partitioned survival model was developed to simulate the lifetime (50 years) incremental cost-effectiveness ratio (ICER) of OLA versus RS from a healthcare payer perspective. Progression-free and overall survival curves were estimated using data from SOLO1 and extrapolated beyond the trial period using parametric survival models. Any patient who remained progression-free at year 7 was assumed to be a long-term survivor and no longer at risk of progression. Mortality rates for this group were modelled on all-cause mortality from the general population adjusted for BRCA1/2 mutation status. These assumptions were validated with local clinicians. Health state utilities and adverse event frequencies were obtained from SOLO1. Drug costs were sourced from local public healthcare institutions. Healthcare resource usage and costs were based on local clinician input and publications. A 3% discount rate was applied to costs and outcomes. Deterministic and probabilistic sensitivity analyses (PSA) were performed to assess the robustness of results. Results: The base-case analysis of OLA maintenance therapy versus RS resulted in an ICER of SGD17, 326 per quality-adjusted life year (QALY) gained. The ICER was most sensitive to variations in the discount rate and mortality risk in long-term survivors. PSA demonstrated that OLA was associated with an 81% probability of being cost-effective at a willingness-to-pay threshold of SGD50, 000 per QALY gained. Conclusions: OLA has a high potential of being a cost-effective maintenance therapy versus RS for patients with BRCA1/2 mutated advanced ovarian cancer after response to first-line chemotherapy in Singapore. Legal entity responsible for the study: AstraZeneca Singapore Pte Ltd. Funding: AstraZeneca Singapore Pte Ltd. Disclosure: D.S. Tan: Honoraria (self): AstraZeneca; Honoraria (self): Novartis; Honoraria (self): Roche; Honoraria (self): MSD; Honoraria (self): Bayer; Honoraria (self): Genmab; Honoraria (self): Tessa Therapeutics; Honoraria (self): Merck Serono ; Research grant / Funding (institution): AstraZeneca; Research grant / Funding (institution): Karyopharm Therapeutics; Research grant / Funding (institution): Bayer; Research grant / Funding (institution): Roche (Foundation Medicine); Research grant / Funding (self): National Medical Research Council Singapore Clinician Scientist Award; Advisory / Consultancy: AstraZeneca; Advisory / Consultancy: Roche; Advisory / Consultancy: Bayer; Advisory / Consultancy: ETC/D3 Singapore; Advisory / Consultancy: Tessa Therapeutics; Advisory / Consultancy: Genmab. J.J. Chan: Honoraria (self): Novartis; Honoraria (self): AstraZeneca; Honoraria (self): Merck Sharp & Dohme; Advisory / Consultancy: Eisai; Advisory / Consultancy: Pfizer; Research grant / Funding (institution): OncoQuest Inc; Research grant / Funding (institution): Pfizer; Travel / Accommodation / Expenses: Synthon; Travel / Accommodation / Expenses: Novartis; Travel / Accommodation / Expenses: AstraZeneca; Travel / Accommodation / Expenses: Celgene. J.K. Loke: Full / Part-time employment: AstraZeneca. R. Hettle: Full / Part-time employment: AstraZeneca. C.C. Yu: Full / Part-time employment: AstraZeneca. All other authors have declared no conflicts of interest.